Perceptions, knowledge, and attitudes towards employee wellness programmes among private high school educators in South Africa - Moroane, Motheo (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Organisations can perform more effectively if their employees' health and wellbeing are optimal and considered a priority. Evidence suggests that employee wellness programmes (EWP) increase employee and overall organisational health, effectiveness, and performance. The World Competitive Report has ranked South Africa poorly regarding Human Resource Management and Development. The South African education system accommodates more than 12,3 million high school learners, 2 938 primary and secondary schools and only 37 500 educators. The South African Department of Education has implemented several initiatives to improve education and the wellbeing of South African educators. However, research investigating the work-related health and wellbeing of educators indicates that burnout, job dissatisfaction, depression, anxiety, and infections, including HIV and AIDS, TB, and Malaria, are prominent among educators. The objectives of this research were to explore whether age, sex, education, and years employed as an educator will significantly impact South African private high school educators' (i) perceptions, (ii) knowledge and (iii) attitudes toward employee wellness programmes, and to (iv) using the answers from a questionnaire; to propose a normative holistic employee wellness programme for private high school educators in South Africa. To fulfil these objectives a mixed-methods study approach was adopted. The study used a once-off, specifically designed questionnaire that explored EWP perceptions, knowledge, and attitudes among South African private high school educators. The results of the questionnaire indicated that firstly, the highest education obtained significantly influenced how educators rated their knowledge of employee wellness programmes. Specifically, the higher the level of education/more educated educators were, the better employees rated their knowledge of wellness programmes. Secondly, gender emerged as a significant factor. Female educators were more inclined to better rate their perception and knowledge regarding whether the workplace could provide valuable source of information on employee health and wellbeing. In other words, female educators rated their knowledge and perceived the workplace as a potentially valuable source of information on employee wellness programmes, than men did. Thirdly, educators with more than ten years of experience were more likely to participate in employee wellness programmes. Lastly, younger employees (younger than the age of 41 years) had the attitude that stigmas may prevent employees from participating in employee wellness programmes and seeking counselling, testing and treatment. Based on these findings, a tailored holistic EWP model was developed to address the specific needs of private high school educators, aiming to enhance their overall wellbeing. In conclusion, this dissertation emphasized the importance of EWP in improving the health and performance of educators in South Africa's private high schools. Importantly, this study identified unique challenges faced by these educators and highlighted the need for tailored wellness initiatives. Lastly, this study emphasizes the importance of addressing educator wellbeing to enhance the overall educational environment in South Africa.
Keywords: Employee health promotion; Employees Health and hygiene; Private schools -- South Africa; Educators -- South Africa Attitudes; Well-being